Francisco Segovia: a poetry of the imminence (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This article wants to realize the language of the evidence that the authoremploys; the article wants to realize the role of witness that has as a poet and the complicity the reader needs which, at the same time, is a witness of the reality that the poet presents. In this sense, I try to establish the resources that privilege the view and that convert this poetry into a faithful example of the language of the evidence.
Keywords: eye; presence; evidence; reality